Spectrum of Laboratory Errors Encountered in the Total Testing Process of a Tertiary Care Teaching Hospital Laboratory - Aman, Saba; Fareed , Noorulain; Mujtaba, Mustajab; Ansari, Uzma; Haneef, Sanam; Ghulam Fatima (Indus Journal of Bioscience Research, 2025)
Background: Monitoring laboratory performance continuously is critical for recognizing errors and promoting further improvements in laboratory. This study aimed to review the laboratory errors in the preanalytical, analytical and post analytical phases of testing in a clinical laboratory. Materials and Methods: A retrospective and descriptive study was carried out at our clinical chemistry, hematology, immunoassay and coagulation laboratories in CHK - Central laboratory Dr. Ruth K.M Pfau Civil Hospital, Karachi, over a period of 1-year period, from November 2022 to November 2023 and the findings of pre-analytical, analytical and post-analytical errors were analyzed of 413631 samples. Results: Errors were detected in 281467 samples out of 413631 samples with total error rate of 68%. Results of the study showed that Preanalytical errors were most common with a frequency of 97.25%, followed by post analytical errors 2.5% and analytical errors 0.25% respectively. Conclusions: The study concludes that pre-analytical, analytical, and post analytical errors arising in laboratory not only lead to wrong diagnosis and treatment of patient they also effect the cost, inventory and human resource as well. The results of our study suggest that more efforts are to be made for training of phlebotomy, sample collection and transport of specimens.